2009
DOI: 10.2353/ajpath.2009.090289
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence in Situ Hybridization Markers for Prediction of Cervical Lymph Node Metastases

Abstract: The presence of lymph node metastases is associated with poor prognosis in early stage cervical cancer. As of yet, no molecular markers predicting lymph node metastases have been identified. We examined single genetic markers and a composite marker, comprised of three fluorescence in situ hybridization (FISH) probes targeting the genes LAMP3, PROX1, and PRKAA1, in pretreatment cervical biopsies from 16 lymph node positive cases and 15 lymph node negative controls from women with stage IB and IIA cervical cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
4

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 41 publications
3
31
0
4
Order By: Relevance
“…Our data show that in these patients, LAMP3 expression is regulated by both genetic gains/amplifications of LAMP3 and tumor hypoxia. Similar to other studies in cervix cancer (38), approximately 40% of all patients showed copy number aberrations and this was associated with increased LAMP3 mRNA and protein expression. However, in the other 60% with no copy number aberrations, we found that hypoxia was strongly and significantly associated with LAMP3 expression.…”
Section: Discussionsupporting
confidence: 72%
“…Our data show that in these patients, LAMP3 expression is regulated by both genetic gains/amplifications of LAMP3 and tumor hypoxia. Similar to other studies in cervix cancer (38), approximately 40% of all patients showed copy number aberrations and this was associated with increased LAMP3 mRNA and protein expression. However, in the other 60% with no copy number aberrations, we found that hypoxia was strongly and significantly associated with LAMP3 expression.…”
Section: Discussionsupporting
confidence: 72%
“…Tumor expression of specific AMPK α, β, and γ subunits in relation to cancer outcomes has been explored in patients with melanoma (87), kidney cancer (85, 86), breast cancer (74), cervical cancer (88), lymphoma (89), ovarian cancer (84, 90, 91), lung cancer (82), and colorectal cancer (92). Total AMPKα1 protein expression, which captures both phosphorylated and non-phosphorylated AMPKα1, was associated with improved overall and disease-specific survival among 128 melanoma patients (87).…”
Section: Ampk Role In Cancer: Human Studiesmentioning
confidence: 99%
“…3,4 The gain of 5p is frequently present in high-grade cervical squamous intraepithelial lesion specimens and is associated with marked dysplasia and cancer. 2,4 These data indicate that the presence of extra copies of these chromosomal loci drives the initial steps of cervical carcinogenesis. [1][2][3][4] In this case, the Cervical DNA Dtex test was used to enumerate genomic copy number for 3q26, 5p15, and centromere 7.…”
Section: Pathologic Findingsmentioning
confidence: 91%
“…2,4 These data indicate that the presence of extra copies of these chromosomal loci drives the initial steps of cervical carcinogenesis. [1][2][3][4] In this case, the Cervical DNA Dtex test was used to enumerate genomic copy number for 3q26, 5p15, and centromere 7. The results showed increased copy number for these markers, indicating extensive DNA damage within these critical regions of the genome.…”
Section: Pathologic Findingsmentioning
confidence: 91%
See 1 more Smart Citation